Aspekty bezpieczeństwa w procesie integracji systemów zarządzania w organizacjach zhierarchizowanych: Safety aspects in the integration of management systems in organizations hierarchical - Wyrębek, Henryk (Management and Administration Journal, 2021)
The goal to achieve and maintain the required level of security is done through theestablishment of adequate accountability mechanisms for monitoring the implementation of therisk and the application of the rules established in terms of the attributes of confidentiality, integrity and availability of information. The key elements of information security management systems in organizations are determined structure of safety management and risk analysis carriedout periodically with a choice of how to deal with the risk. The basis for the proper protection ofinformation assets is inventory defined by the classification of information storage media, sensitive information and communication systems, as well as the same groups of information.